2002
DOI: 10.1359/jbmr.2002.17.11.1968
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protein Kinase C α in Primary Human Osteoblast Proliferation

Abstract: Protein kinase C (PKC) isoforms have been shown to have specific expression profiles and individual isoforms are believed to play distinct roles in the cells in which they are found. The goal here was to determine which specific isoform(s) is involved in proliferation of primary human osteoblasts. In primary human osteoblasts, 10 M of acute sphingosine-1-phosphate (S1P) treatment induced an increase in proliferation that correlated with an increase in PKC␣ and PKC expression. To further delineate which isoform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
3
19
1
Order By: Relevance
“…The expression of PKC · continued to increase throughout the proliferative stages of MC3T3-E1 OBC. This pattern of expression is in accord with previous studies (22,31). In primary rat OBC there is a continuous increase in PKC · expression from early to late cell cultures.…”
Section: Discussionsupporting
confidence: 92%
“…The expression of PKC · continued to increase throughout the proliferative stages of MC3T3-E1 OBC. This pattern of expression is in accord with previous studies (22,31). In primary rat OBC there is a continuous increase in PKC · expression from early to late cell cultures.…”
Section: Discussionsupporting
confidence: 92%
“…3 H]-thymidine using a methodology previously described for osteoblastic cells from the alveolar bone (13). Once the cell cultures from the donor bones reached 70% confluency, they were detached by trypsinization and cultured in 24-well plates at a density of 50,000 cells/well.…”
Section: 25(oh)mentioning
confidence: 99%
“…It has been reported that the protein kinase C (PKC) signalling pathway is involved in osteoblast proliferation and differentiation [98][99][100]. Thus, in chapter 2, we have investigated the role of the PKC family in the context of hMSCs osteogenic differentiation in vitro.…”
Section: Aims and Outlines Of This Thesismentioning
confidence: 99%
“…Some reports show that certain PKC isozymes are involved in osteogenic differentiation or osteoblast proliferation. For instance, PKCδ and PKCμ, are known to be involved in osteogenic differentiation in murine cells and animal models and PKCα has been implicated in human osteoblasts proliferation [98,100,144]. We treated hMSCs with PKC activators and inhibitors to investigate cell proliferation and differentiation in vitro, and observed that different PKC subfamilies had opposite roles in ALP expression and mineralization.…”
Section: Improving Hmsc Osteogenic Differentiationmentioning
confidence: 99%
See 1 more Smart Citation